Industrial relations practices related to psychosocial constraints at work in the steel sector - Agostini, Michel; Bauchiere, Didier; Beaufort, Philippe; Montreuil, Elodie; Van Criekingen, Liesbeth; Weingarten, Jörg (Dublin, 2014)
"This report looks at industrial relations practices regarding health and safety strategies in the European steel sector. The findings are based on desk research and a comparative analysis of company practices in three company case studies: ArcelorMittal in France, Rautaruukki in Finland and Salzgitter AG in Germany. The report offers a transversal analysis, examining the main findings on the role of social dialogue and company practices regarding prevention while also highlighting some specific company and sectoral features triggering psychosocial risks and their prevention. Each of the three case studies presents the company’s strategies for assessing and preventing psychosocial issues at work and examines the involvement of the workers or workers’ representatives. Two of the three case studies concern company pilot sites involved in addressing psychosocial constraints at work."